Descriptions et affinités d'une éponge sphinctozoaire actuelle. In: Lévi C, Boury-Esnault N (eds) Biologie des Spongiaires. Sponge Biology. - Vacelet, J. (Colloques Internationaux du Centre National de la Recherché Scientifique, Paris, 1979)
A 'living fossil' of the group Sphinctozoa has been discovered in the Indian Ocean and in New Caledonia in a very cryptic habitat of the outer slope of coral reefs. ...
Proceedings of the 2nd International Sponge Conference